PELAKSANAAN BIMBINGAN PRANIKAH BAGI CALON PENGANTIN PENYANDANG DISABILITAS - Innaiyah Humairah; Yusida Fitriyati (Usroh: Jurnal Hukum Keluarga Islam, 2023)
Pre-wedding guidance is a mandatory series for every bride and groom who will get married. However, in its implementation in several KUA in Palembang there are still many prospective brides with disabilities who do not receive premarital guidance. Persons with disabilities have the same right to get the opportunity to take part in pre-marital counseling as bride and groom in general so that justice is created for all Indonesian people. The research method used is qualitative research with an empirical normative approach. This study aims to find out the implementation of premarital counseling for brides with disabilities at the KUA in Palembang city and to explain the review of Islamic law on its implementation. The results obtained from this study were that the implementation of premarital guidance for brides with disabilities at KUA Ilir Barat I, Ilir Barat II and Bukit Kecil was not effective because there were no specific rules governing the implementation of premarital guidance for persons with disabilities so that the organizers lacked preparation. However, on the other hand, prospective brides with disabilities already have the same rights as ordinary brides so they can attend marriage counseling at the KUA. According to Islamic law, the implementation of pre-marital guidance can be categorized as maslahah in order to achieve justice for prospective brides with disabilities in participating in marriage counseling at the KUA and are treated the same as ordinary brides. Keywords: Premarital Guidance; Persons with Disabilities; KUA